PENGARUH PENAMBAHAN BUAH MENGKUDU TERHADAP KUALITAS ES KRIM - Alersa1,, Firna Agus; Faridah, Anni; Syarif, Wirnelis (Journal of Home Economics and Tourism, 2017)
This event will be based on research by the utilization of the noni fruit is still a bit and less liked by the people. This research aims to analyze the effect of the addition of the noni fruit to the quality of the ice cream covering, color, aroma, texture, and flavor. This type of research is a pure experiment with a random design complete method uses three repetitions with 30 panelists were implemented in June 2017 on the workshop Tata Boga. The free variable (X) is the addition of noni fruit as much as 0% (x 0), 10% (X 1), 20% (X 2), 30% (X 3), variable (Y) is the external quality of noni fruit. The instruments used are the now then analyzed with organoleptic. The data already acquired and then tabulated in the form of tables and do the analysis Variant (ANAVA). If different test followed by Duncan. The results showed that there was a real influence on quality of colour, the aroma of creamy milk, noni fruit aroma, sweetness, and the flavors were not typical fruit of mengkudu.Keywords: Noni Fruit, Ice Cream, Quality.